Response Mechanism of the Phase Transitions of Poly(N-Isopropylacrylamide-Co-Benzo-18-Crown-6-Acrylamide) Using Infrared Spectroscopy. Issue 8 (August 2014) - Han, Xiaoyan; Xiao, Peipei; Zhao, Hong; Zeng, Chuyi; Zhou, Jicheng
The thermal and ionic effects on the phase transitions of poly( N -isopropylacrylamide) (PNIPAAm) and its copolymer with benzo-18-crown-6-acrylamide, poly( N -isopropylacrylamide-co-benzo-18-crown-6-acrylamide) (PNIPAAm-co-BCAm), were investigated using infrared (IR) spectral variations of methyl (CH3 ), C=O, and amine (NH) groups. Subsequently, perturbation correlation moving-window two-dimensional correlation infrared spectroscopy (PCMW 2D-IR) was applied to clarify the differences in the phase-transition mechanisms of the polymers. The dominant influence on the phase-transition mechanism of PNIPAAm is whether the anion is evenly distributed in the bulk solution. The results show that the phase transition shifts to a lower temperature with increasing barium chloride (BaCl2 ) concentrations. In addition, the effect of the anion on the chemical group is homogeneous upon heating. As a result, the relevant transition temperature ranges have remain approximately constant. In contrast, the dominant influence on the phase-transition mechanism of PNIPAAm-co-BCAm is the interactions of the polymer chains with barium ions (Ba 2+ ). The hydrophilic BCAm–Ba 2+ complexes distributed in the PNIPAAm-co-BCAm chain prevent the water molecules from leaving the polymer chains, which leads to an increase in the transition temperature and the complicated variation of the transition temperature range, as environmental stimuli–response behavior, with increasing BaCl2 concentrations.